HANNAH ARENDT: PHILOSOPHER IN TIMES OF PERPLEXITY - Rodríguez Cruz, Manuel; Amorim Lima, Adenaide (Revista Binacional Brasil-Argentina: Dialogue between the sciences, 2023)
After a first commentary about Arendt’s reception in Spain, the author raises the possibility to use the main categories of The human condition in order to approach the problem of human subjectivity in the adequate terms for present times. It is a question of considering all those determinations without which it would not be possible to analyse the problem of identity today: action, fragility, natality, recognition. Likewise, it is tried to escape from all those ideals of perfection which were accepted long ago with the title of utopia, and which ended up by reveal themselves – as Arendt suffered in the flesh – as the basic cause of four time’s greatest horrors.